Acceptability of a hypothetical dengue vaccine and the potential impact of dengue vaccination on personal vector control behavior: a qualitative study in Fortaleza, Brazil - Valerie K. Scott; Maria Suelly Nogueira Pinheiro; Marcia Maria Tavares Machado; Marcia C. Castro (BMC, 2023)
Abstract Background Dengue is the most rapidly spreading viral vector-borne disease in the world. Promising new dengue vaccines have contributed to a growing consensus that effective dengue control will require integrated strategies of vaccination and vector control. In this qualitative study, we explored the perspectives of residents of Fortaleza, Brazil on acceptability of a hypothetical safe and effective dengue vaccine, specific drivers of dengue vaccine acceptance or hesitance, and the expected impact of dengue vaccination on their personal vector control practices. Methods A total of 43 in-depth interviews were conducted from April to June 2022 with Fortaleza residents from a diverse range of educational and professional backgrounds, with and without recent personal experiences of symptomatic dengue infections. Data were analyzed using the principles of inductive grounded theory methodology. Results Our findings indicate that knowledge of dengue transmission, symptoms, and prevention methods was strong across respondents. Respondents described willingness to accept a hypothetical dengue vaccine for themselves and their children, while emphasizing that the vaccine must be demonstrably safe and effective. Respondents expressed diverse perspectives on how receiving a safe and effective dengue vaccine might influence their personal vector control behaviors, relating these behaviors to their perception of risk from other Aedes mosquito-carried infections and beliefs about the role of vector control in maintaining household cleanliness. Conclusions Our study findings provide community-level perspectives on dengue vaccination and its potential impact on personal vector control behavior for policymakers and program managers in Fortaleza to consider as new dengue vaccines become available. With the introduction of any new dengue vaccine, community perspectives and emerging concerns that may drive vaccine hesitancy should be continuously sought out. Improved urban infrastructure and efforts to engage individuals and communities in vector control may be needed to optimize the impact of future dengue vaccinations and prevent rising cases of other arboviruses such as Zika and chikungunya.